Advances in Induction and Microwave Heating of Mineral and Organic Materials - Grundas, Stanislaw (InTechOpen, 2011)
The book offers comprehensive coverage of the broad range of scientific knowledge in the fields of advances in induction and microwave heating of mineral and organic materials. Beginning with industry application in many areas of practical application to mineral materials and ending with raw materials of agriculture origin the authors, specialists in different scientific area, present their results in the two sections: Section 1-Induction and Microwave Heating of Mineral Materials, and Section 2-Microwave Heating of Organic Materials.
Keywords: Induction; Microwave Heating; Mineral And Organic Materials